Targeted temperature management evolving over time—A local process analysis. Issue 9 (16th August 2022) - Strålin, Axel; Thuccani, Meena; Lilja, Linus; Rylander, Christian
Abstract: Background: Post‐resuscitation care of comatose survivors from cardiac arrest includes target temperature management (TTM) to mitigate cerebral reperfusion injury. High‐quality TTM requires protocols enhancing good precision. This study explored how the quality of TTM may have evolved with increasing experience from clinical trial protocols and standard operating procedures. We hypothesized that there would be a positive effect over time, detectable between trial periods and between trial periods and later everyday practice. Methods: Three TTM quality parameters were defined: time to target, temperature variability, and fever incidence. Data from 181 patients treated during three different time periods in a tertiary center were analyzed; 45 from Period 1 (local trial cohort 2011–2013) targeting 33°C or 36°C; 76 from Period 2 (local trial cohort 2018–2020) targeting 33 or <37.5°C; 60 from Period 3 (current standard operating procedure 2020–2021) targeting 36°C. Groups of similar target temperatures from different time periods were compared using ordinary group statistics. Results: TTM quality in all three parameters increased between trial periods. There were no differences in TTM quality as to temperature variability or fever incidence between the <37.5°C Period 2 and the 36°C Period 3 groups. A 33°C target temperature was associated with lower fever incidence than 36°C and <37.5°C target regimes. Conclusion: The observed increase in TTM quality in this single‐center study may be a result of increased competence through learning and training in different strict TTM protocols. If so, the results of this study further support the protocolization of post‐cardiac arrest intensive care.